One-year monitoring of a reinforced concrete school building: Evolution of dynamic behavior during retrofitting works. (2017) - Pierdicca, A.; Clementi, F.; Mezzapelle, P.; Fortunati, A.; Lenci, S.
Abstract: This work illustrates the results of a one-year structural monitoring campaign of a Reinforced Concrete (RC) school building subjected to a substantial retrofitting works. Through Operational Modal Analysis (OMA) techniques, it has been possible to follow the dynamic evolution of the structure, using Finite Element Method (FEM) model refinement as a valuable tool for non-invasive structural assessment. The long-term Ambient Vibration Survey (AVS) highlighted the increasing of building performance in terms of natural frequencies following the retrofitting works. This relevant data collection can be extremely helpful in calibrating of other similar retrofitting interventions and provides useful guidelines that can assist in the planning of Structural Health Monitoring (SHM) applications.